Exploring the Justice Paradox in Clemency for Narcotics Convicts: A Case Study of Banyuasin Class IIB Prison - Dodis Nikmatulo; Ruben Achmad; Arief Wisnu Wardhana (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
The granting of clemency as a presidential prerogative within the Indonesian legal system has sparked considerable debate, particularly when applied to narcotics offenders classified as perpetrators of hard crimes. This study examines the case of Muhammad Aldin Purwanto, a narcotics convict who was granted clemency in the form of sentence reduction, despite having previously been sentenced to seven years' imprisonment for acting as an intermediary in the sale of a Schedule I narcotic substance. Clemency was granted on the grounds of good behavior and his role as the primary breadwinner for his family. This research aims to analyze the granting of clemency within the framework of justice, employing a normative juridical method with both conceptual and case study approaches. The study reveals a tension between the principle of retributive justice, which demands proportionate punishment for criminal acts, and the restorative justice approach, which emphasizes offender rehabilitation. The clemency granted in this case presents both a moral and legal dilemma, as it may be interpreted as a denial of retributive justice and a dilution of the meaning of criminal responsibility. The findings suggest that the absence of clear parameters for granting clemency creates vulnerabilities to policy deviation, potentially undermining the legitimacy of the criminal justice system itself. Therefore, a reformulation of clemency policy is necessary through clearer legal regulation, grounded in justice-based principles. Clemency should be guided by rational, objective, and balanced legal considerations that weigh both the rights of the convict and the public sense of justice.